The Role Of Islamic Religious Education As Mental Health Therapy: A Review Of Viktor Frankl's Logo Therapy - nakhma nakhma ussolikhah; Widodo Winarso (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
The aim of this research is to help students deal with mental health in the university environment. This research approach uses the qualitative method of social phenomenology. Data collection was carried out through interviews, observations, and mental health measurement instruments using open interviews. The research subjects, 25 students, were screened at the beginning, but they could be adjusted based on indicators of symptoms of mental disorders, there were 5 UI BBC students, of the 5, 3 received special treatment based on the high level of mental disorders, 2 were UNU students and 2 were UIN SSC students. The research results show that Islamic education can be improved with the concept of logotherapy which emphasizes the meaning of life. student mental health. This intervention emphasizes emotional expression, spiritual meaning, and strengthening Islamic values. The trial showed significant improvements in students' mental health scores after attending counseling sessions. Intensive training is needed for student counselors to apply this model in various universities. Additionally, further research is recommended to adapt this model for other populations with similar needsKeywords: Islamic Religious Education, Mental Health, Logo Therapy.